DESAIN MODUL PRAKTIKUM MANDIRI TENTANG GERAK PARABOLA MENGGUNAKAN SIMULASI PhET”PROJECTILE MOTION” - Liyensi Karanggulimu; Debora Natalia Sudjito; Diane Noviandini (Universitas Muhammadiyah Semarang, 2017)
Learning about projectile motion is sometimes limited by time and tools which makes student can not understand the concepts in projectile motion. Therefore, lab work is a suitable medium to help students learn independently and give them chances to explore the learning materials further. Nowadays, there is a lab work application called PhET simulation. Lab work needs module to make learning process be structured and easy to understand. This research aims to investigate (i) how to design a lab work module about projectile motion using PhET simulation; (ii) how effective that lab work module to help students understand the concept of projectile motion. This qualitative descriptive research was using 5 college students of Physics Education Batch 2016 as respondents.Lab work module was implemented and observed by observers, and then students were assigned to do post˗test and fill the questionnaire. The results were (i) 80% students obtained evaluation score more than 70 with the mean of 100; (ii) 100% respondents were very enthusiastic during the lab work; (iii) 100% respondents showed positive respond in the questionnaire. Thus, it could be concluded that the utilization of lab work module using PhET simulation is effective to help students understand about projectile motion.Keywords: projectile motion, PhET simulation, module, lab work